A safety evaluation of pirfenidone for the treatment of idiopathic pulmonary fibrosis. Issue 7 (2nd July 2016) - Anderson, Adam; Shifren, Adrian; Nathan, Steven D.
ABSTRACT: Introduction : Pirfenidone is a novel oral anti-fibrotic agent approved for the treatment of idiopathic pulmonary fibrosis (IPF). Since IPF is a chronic and progressive disease most commonly encountered in an older population, therapeutic options should be not only effective, but also free from drug interactions and as safe and tolerable as possible. Areas c overed : Comprehensive data from randomized controlled trials, meta-analyses, safety studies, and post-marketing data are available to assess the efficacy and safety of pirfenidone in the treatment of IPF. Information on efficacy, adverse events, drug tolerability and discontinuation rates both in clinical trials and real-world clinical experiences are reported. Expert opinion : Pirfenidone has an abundance of data supporting its use in mild-to-moderate IPF. Observational evidence suggests a similar efficacy in severe IPF. In clinical trials, observational studies and real-world use, adverse events are frequent, though generally mild and well tolerated, especially with adequate patient education. Preventative strategies, along with timely and appropriate management of adverse events are critical in improving patient compliance, thereby ensuring the benefits of long-term treatment with pirfenidone.